Value Orientations of Modern Entrepreneurship in Russia - Korneiko Ol’ga V. (Economic and Social Changes: Facts, Trends, Forecast, 2017)
In the theory of entrepreneurship there is a distinct conviction that the value system of entrepreneurs and their behavior have an impact on economic efficiency and, ultimately, on the welfare of the whole society. The issues related to the description of professional and personal qualities of Russian entrepreneurs, their values and motivations, are currently becoming more and more relevant. The development and enrichment of national scientific knowledge in Russian entrepreneurship will largely determine our understanding of its effectiveness for the Russian economy. In domestic literature, there is clear shortage of works devoted to this problem, which is caused by limited capabilities of existing databases. This article attempts to identify the hierarchy of values and their structure in the form of broader orientations in economic behavior of Russian entrepreneurs in the case of fishery business enterprises in Primorsky Krai. Based on an interdisciplinary synthesis, the research proves that the modern theory of entrepreneurship does not only accept the concepts of scientific masterminds, but also enriches their meaningful interpretation. The author reviews the existing approaches to measuring values. The analysis presented in the article is conducted on the basis of observations during visits to fishery enterprises of the region, questionnaires and in-depth interviews of coastal entrepreneurs specializing in fishery. It has been established that the “external” values are currently more important in the hierarchy of values for coastal entrepreneurs than the “internal” ones despite their considerable affinity. With the individualistic value dominant element available, we can talk about strong social focus and the focus on “basic” values. This study makes it possible to characterize a modern Russian entrepreneur as a civilized, socially responsible personality motivated by an internal system of values. We propose to introduce into scientific circulation the category of “ethical entrepreneurship”, i.e. the implementation of activities based not only on economic benefits, but also under the influence of “basic” values (integrity, honesty, and responsibility) and social focus. The study is presented as a pilot one and suggests further in-depth development of the methodology taking into account the obtained results